Design of network device driver in embedded Linux - Yongxiang Guo; Wu Deng (2010 International Conference on Computer Application and System Modeling (ICCASM 2010), 2010)
With the widely application of ARM technique, building the embedded operating system based on ARM processor has been a hot point of research. In this paper, the design of network device driver in Linux operating system based on ARM920T processor is implemented on the S3C2410- S development platform made in Beijing universal pioneering technology. Focused on discussing implementation principle of embedded Linux network drivers and detailed to analysis of the frame structure of the program code.